2010
DOI: 10.1007/s11244-010-9588-3
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of SAPO-34 Crystals with Different Morphologies by Microwave Heating

Abstract: The crystal size and shape of the silicoaluminophosphate molecular sieve SAPO-34 have been effectively controlled in the reaction system of Al 2 O 3 -P 2 O 5 -SiO 2 -TEAOH-H 2 O under microwave radiations. Nano sheet-like SAPO-34 crystals are obtained when using colloidal silica as the silica source. When TEOS is used as the source of silica, homogeneous SAPO-34 crystals with a particle size of about 100 nm are formed, and the morphology of the crystals changes from uniform nano particles (*100 nm) to microsph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 25 publications
1
51
0
Order By: Relevance
“…SAPO-34 was synthesized by microwave heating as reported by Lin et al 20 . The composition of the synthesis gel was 1 Al(OPri)3 : 2 H3PO4 : 0. hours.…”
Section: Synthesis Of Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…SAPO-34 was synthesized by microwave heating as reported by Lin et al 20 . The composition of the synthesis gel was 1 Al(OPri)3 : 2 H3PO4 : 0. hours.…”
Section: Synthesis Of Materialsmentioning
confidence: 99%
“…An increase in rate of diffusion can be achieved by preparing CHA type materials with smaller crystalline size. For doing that, a dry gel synthesis method 15 , the use of a combination of different SDA [16][17][18][19] , as well as the use of microwaves 20,21 has been applied to the synthesis of SAPO-34 with the objective of enhancing lifetime of the catalyst for the reaction of methanol to olefins. It has been found that a combination of TEAOH and morpholine in the synthesis results in a decrease of the size of the crystals with the corresponding increase in lifetime 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanosized SAPO-34 catalysts were prepared under microwave radiations following previously reported method by using colloidal silica or TEOS as the silicon source. 24 The SAPO-34 catalysts with medium and ordinary size were obtained with Na 2 SiO 3 solution as the silicon source under hydrothermal or microwave-assisted conditions. Typically, the finely ground Al(OPr i ) 3 was first mixed with TEAOH solution and deionized water at room temperature until dissolved completely.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the catalyst life of SAPO-34 can be improved by decreasing the crystallite size without varying the acid amount due to the improvement in the mass transfer inside the pores of the catalyst [7,13]. The synthesis of smaller-sized SAPO-34 compared with SAPO-34 synthesized by the conventional method has been attained by using various approaches, such as dry-gel method and microwave-assisted heating [14][15][16][17][18][19][20][21][22]. These smaller-sized SAPO-34 catalysts exhibited a longer catalyst life compared with the conventional SAPO-34 catalyst in the MTO reaction.…”
Section: Introductionmentioning
confidence: 99%